Diglosia Bahasa Arab Pesantren dan Upaya Pemertahanan Bahasa Daerah - Wahyu Hanafi Putra (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2017)
The purpose of this study is to describe the diglossia of Arabic pesantren and its influence on regional language defense, as well as providing a resolution to the pesantren in maintaining the regional language. The research method used is descriptive qualitative. The result of this research is that the existence of diglossia Arabic pesantren which is done consistently can influence the defense of local language of speech in pesantren. The solution for pesantren in maintaining the regional languages is to establish a language center, reschedule language activities, hold language festivals, give appreciation and cultivate a sense of pride towards its speakers. Keywords: Diglossia, Arabic Language, Pesantren, Regional Language